editsa
contestada

Please help ASAP
What are the equations of the asymptotes of the hyperbola?

(y+4)^2/36−(x−6)^2/49=1

Enter your answer in point-slope form. Enter the slope as a simplified fraction.

Respuesta :

Answer:

The answer to your question is below

Step-by-step explanation:

             [tex]\frac{(y + 4)^{2} }{36} + \frac{(x - 6)^{2} }{49} = 1[/tex]

a² = 36             a = 6

b² = 49             b = 7

asymptotes  

                   y = ± [tex]\frac{b}{a} x[/tex]

                  y = [tex]\frac{7}{6} x[/tex]

                   6y = 7x

                   y = [tex]\frac{-7}{6}x[/tex]

                   6y = -7x

                 

ayo it's y+4=(the plus and minus sign thingy) 6/7(x-6)

hope this helps :]